Genetic variation for micronutrients and study of genetic diversity in diverse germplasm of rice - Tripathy, S. K. (Crop and Weed Science Society, 2020)
An experiment was carried out to explore high iron (Fe) and zinc (Zn) donors, and to study the extent of genetic divergence based on such micronutrients and agro-morphological traits including seed yield in a set of 92 diverse germplasm lines of rice. Grain Fe (8.3-52.15ppm) and Zn content (3.0-52.7ppm) revealed wide variation among the germplasm. P44 mutant selection- 1, ORCZ 75-3-1, Basudha, Malliphulajhuli, Tikimahsuri and Nikipankhia were rich in both Fe and Zn. P44 mutant selection- 1 and ORCZ 75-3-1 had high yield potential while above local land races were poor yielding. The total set of genotypes were grouped into 12 distinct clusters. Jabaphulla, Parijat and Sakaribanki emerged as most divergent genotypes, but moderate low in Fe and Zn content. Interestingly, most of the local land races and the breeding lines clubbed into two separate distinct clusters respectively. The Fe and Zn dense genotypes identified above belong to the same distinct single cluster that showed high Fe and Zn content. Hence, such donors may serve as valuable material for Fe and Zn biofortification breeding.